Assessing Psychosocial Health Impacts of Climate Adaptation: A Critical Review. (May 2023) - Miller, Mary E.; Nwosu, Chijioke O.; Nyamwanza, Admire M.; Jacobs, Peter T.
The urgency of dealing with risks associated with climate change and the need for effective response measures to their impacts are increasing daily the world over. Literature abounds regarding the impacts of climate change on physical, psychosocial, and other health outcomes. In contrast, little research exists on the health impacts of response measures to climate change. This critical review seeks to contribute towards closing this gap through a synthesis of current literature on the psychosocial health outcomes of climate adaptation actions. Our results found both positive and negative outcomes associated with psychosocial health that may result from climate adaptation actions. We propose the utilization of well-developed conceptual frameworks and evaluation tools in assessment and analysis of these outcomes. Ultimately, there is need to expand similar and related areas of research more broadly and on psychosocial effects, specifically.